THU0335 Acetylcholinesterase is highly expressed in the inflamed vessel wall of patients with giant cell arteritis. (15th June 2017) - Therkildsen, P; Nielsen, BD; Keller, KK; Steiniche, T; Gormsen, LC; Hansen, IT; Hauge, E-M
Abstract : Background: The temporal artery biopsy (TAB) remains the gold standard in the diagnosis of giant cell arteritis (GCA) and is part of the ACR Classification criteria for GCA. However, TABs are false-negative in 10–60% of cases [1]. Cellular studies have shown that activated immune cells upregulate the acetylcholinesterase (AChE) expression [2]. If AChE is upregulated in the active GCA vessel wall, it may potentially improve the TAB as a diagnostic tool. Objectives: To investigate the in-situ expression of acetylcholinesterase (AChE) in the vessel wall of patients with biopsy-positive GCA and compare to non-GCA patients. Methods: In this histological case-control study, TABs from a total of 24 TAB-positive GCA and 44 TAB-negative non-GCA patients (21 patients with a final diagnosis of PMR, 23 patients with other diagnosis) were retrospectively selected from TABs performed between January 2012 and December 2015. A total of 295 TABs were assed for inclusion. Only positive TABs showing clear transmural inflammation were included. Patients treated with >7 days of prednisolone prior to the TAB were excluded. Clinical data were obtained from electronic patient records to confirm or dismiss clinical diagnosis. TAB-HE-stains were reviewed by a pathologist with expertise in vasculitis. Immunohistochemical methods were used to determine the AChE expression. The histological inflammation and AChE expression were assessed and graded on 0–1-2 scale, blinded to histological and clinical data. Solitary AChE staining of the media was not included in the assessment. Results: 24 positive and 44 negative TABs, with corresponding clinical positive and negative GCA diagnosis, were included in this study. We found that 10/24 positive TABs showed high AChE expression (grade 2) and 14/24 showed moderate AChE expression (grade 1). No AChE expression was observed outside the media in negative TABs from non-GCA patients (i.e. grade 0). The AChE expression was in 79% agreement with the degree of histological inflammation with a kappa value of 0.58. Prednisolone treatment for up to 7 days did not suppress the AChE expression. Neither the AChE expression, nor the histological inflammation showed correlation to any clinical or biochemical findings. Conclusions: Our study shows that high to moderate AChE expression was observed in all 24 biopsies from TAB-positive GCA patients and that the AChE expression was in good agreement with the histological inflammation. No non-specific AChE expression was observed outside the media in any of the 44 TABs from TAB-negative non-GCA patients. This indicates that AChE could play a significant role in the inflammatory process in GCA and may be a potential biomarker in inflammatory diseases such as GCA. References: Luqmani, R., et al., The Role of Ultrasound Compared to Biopsy of Temporal Arteries in the Diagnosis and Treatment of Giant Cell Arteritis (TABUL): a diagnostic accuracy and cost-effectiveness study. Health Technol Assess, 2016. 20(90): p. 1–238. Fujii, T., et al., Expression of acetylcholine in lymphocytes and modulation of an independent lymphocytic cholinergic activity by immunological stimulation. Biogenic Amines, 2003. 17(4–6): p. 373–386. Disclosure of Interest: None declared